MANAJEMEN SUMBER DAYA MANUSIA - ERI SUSAN (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2019)
Abstract. Human resources (HR) is one of the most important factors that cannot even be separated from an organization, both institutions and companies. HR is also a key that determines the development of a company. In essence, human resources in the form of people employed in an organization as a mobilizer, thinker and planner to achieve the goals of the organization. Therefore, human resources need to be managed effectively through the implementation of HR management functions is a matter relating to the empowerment of humans in carrying out a job to achieve the maximum level or effective and efficient in realizing the goals to be achieved in the company, an employee and also the public.